ANALYSIS OF ECONOMIC GROWTH AND DEVELOPMENT INEQUALITY AMONG DISTRICTS/CITIES IN WEST NUSA TENGGARA PROVINCE USING THE WILLIAMSON INDEX, KLASSEN TYPOLOGY, AND LOCATION QUOTIENT METHODS - Purnamasari, Nur Asmita; Hadijati, Mustika; Hidayati, Lilik; Saputra, Dede; Graha, Syifa Salsabila Satya (VARIANCE: Journal of Statistics and Its Applications, 2025)
West Nusa Tenggara Province faces low GRDP growth and significant economic disparities among its districts and cities. This study aims to analyze economic growth and development inequality using the Williamson Index, Klassen Typology, and Location Quotient methods. The Williamson Index shows high inequality, with values approaching 1 from 2018 to 2022. Klassen Typology categorizes districts into four quadrants: fast-growing (West Sumbawa, Mataram City), developing (Dompu, Bima City), developed but under pressure (West Lombok, Central Lombok, East Lombok, Sumbawa, Bima, North Lombok), and none in the underdeveloped category. The Location Quotient analysis highlights sectors with growth potential; however, some regions still rely on imports to meet local demand. The findings suggest targeted policies to enhance sector development and reduce economic disparities, fostering sustainable growth and improving welfare in West Nusa Tenggara Province.